A magyar közigazgatás elméleti háttere, kihívásai és aktuális kérdései a XXI. században (Theoretical Background, Challenges and Current Issues of Hungarian Public Administration in the 21st Century) - András Torma (KözigazgatásTudomány)
In the age of the information society, the question is not whether there is information, but how we can find it. The growing administrative tasks not only provide society with more information, but also require more information. By the 21st century, it has become clear that the current perception of government and public administration in developed countries needs to be changed through reform, because the increasing scale of information production and acquisition demands it. Reforms have been (are being) implemented along three models: the technical, the value and participation and the regulatory approaches. The paper presents the characteristics of these theoretical approaches and then examines the Hungarian reforms after the regime change of 1989/1990. For the post-2010 reforms, it concludes that ours is a fourth, a peculiarly Hungarian approach, best described by the adjective 'unorthodox'. In order to justify this, it presents the specific Hungarian solutions implemented in the organisation and functioning of central, regional and local public administration. The final conclusion is that the Hungarian reforms have been successful, but by no means that all is well with their implementation. However, new research is needed to identify and quantify the problems, the results of which could be published in a new study.